Clinical experience of biliary T tube of immobilization of peri-pin membrane in tibial Gustilo III fracture treated with vacuum sealant drainage combined with an external fixator. Issue 43 (23rd October 2020) - Ye, Hui; Lin, Shufeng; Zhu, Junfeng; Jiang, Lifeng
Abstract: Objective: To determine the effects of an improved method of peri-pin membrane immobilization in tibial Gustilo type III fracture treated with vacuum sealant drainage (VSD) combined with an external fixator. Method: A biliary T tube of suitable size and type was cut into a certain long arm and cross arm which wrapping around a pin to improving traditional peri-pin VSD method. Eighty-six cases of Gustilo type III tibial fracture admitted from January 2016 to December 2019 were prospectively treated, of which 43 cases were treated using a traditional method of VSD (Traditional group) and 43 cases in which VSD treatment was enhanced (Improved group). The 2 groups were compared by some clinical indexes. Statistical software was then used for data analysis. P < .05 was considered statistically significant. Results: Compared with the Traditional group, the improved group significantly reduced granulation tissue growth time (day) (7.35 + 2.59 vs 11.14 + 2.54, P < .05), antibiotic use time (day) (6.67 + 2.39 vs 8.70 + 1.98, P < .05), operation time (min) (72.44 + 16.79 vs 85.47 + 17.44, P < .05) duration of hospital stay (day) (18.23 + 5.04 vs 21.53 + 4.79, P < .05), wound closure time (day) (9.23 + 2.69 vs 14.19 + 2.67, P < .05), air leakage around the fixed needle (3/43 vs 16/43, P < .05) and postoperative pain score ( P < .05). Meanwhile, the white blood cell, C-reactive protein, erythrocyte sedimentation rate of 1 week and 2 weeks post-operation were also reduced after adopting the improved method ( P < .05). The difference in infection around the fixation pin and pin loosening between the 2 groups was not significant. Conclusion: The biliary T tube was effctive in improving VSD combined with external fixation for the treatment of tibial Gustilo type III fractures. The materials are easy to obtain and straightforward to use and so is worthy of clinical promotion.